2015
DOI: 10.5195/cajgh.2015.187
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Tobacco Use Among Undergraduate and Postgraduate Medical Students in India: A Multicentric Cross-sectional Study

Abstract: Background:Substance use among medical fraternity is a well-known phenomenon among both undergraduate (UG) and postgraduate (PG) medical students. Yet, there have been very few multi-centric studies to estimate the actual burden of this problem in this important population group in India. This study was conducted to estimate the prevalence of alcohol and tobacco use, assess the knowledge and attitudes towards this issue, and identify factors associated with substance use among UG and PG medical students in Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 12 publications
(24 reference statements)
2
24
1
Order By: Relevance
“…A multi-centric study across eight medical colleges of India showed the prevalence of alcohol consumption increased from 16.7% in undergraduate medical students to 31.5% in postgraduates, rate being higher in males. [20] However, even in our study, the alcoholic category had 20.4% more students with HOMA-IR>=2 as compared to non-alcoholic or abstaining students. The study was limited by its sample size, which prevented a more detailed stratified or re-gressional analysis of the confounders.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…A multi-centric study across eight medical colleges of India showed the prevalence of alcohol consumption increased from 16.7% in undergraduate medical students to 31.5% in postgraduates, rate being higher in males. [20] However, even in our study, the alcoholic category had 20.4% more students with HOMA-IR>=2 as compared to non-alcoholic or abstaining students. The study was limited by its sample size, which prevented a more detailed stratified or re-gressional analysis of the confounders.…”
Section: Discussionmentioning
confidence: 41%
“…[18] Garg et al [19] reported 71.9% students started alcohol consumption after admission to a medical college, a third of which developed regular frequency. Goel et al [20] reported 16.7% alcoholism in medical students with higher prevalence in males. Prevalence of alcoholism found in our study is higher and could be a reflection of the higher socio-economic status of the students.…”
Section: Discussionmentioning
confidence: 99%
“…Hazardous and dependence level of drinking were seen more in males than females (76.1% and 87.5% respectively), which is similar to findings from other studies. [24,25,26] While hazardous drinking was more prevalent in final year (40.3%), dependence was equally present in second and final year. Hazardous (41.8%) and dependence (56.3%) level of drinking were seen more in those students who had failed once since joining the course.…”
Section: Alcoholmentioning
confidence: 99%
“…[1][2][3][4][5] Many medical students in the United Arab Emirates were aware that their diet was unhealthy. 6 A majority of female Chinese University students with low body mass index (BMI) indicated a desire to be thin.…”
Section: Introductionmentioning
confidence: 99%